2012
DOI: 10.1080/0305215x.2011.639370
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective ant colony optimization for the twin-screw configuration problem

Abstract: The Twin-Screw Configuration Problem (TSCP) consists in identifying the best location of a set of available screw elements along a screw shaft. Due to its combinatorial nature, it can be seen as a sequencing problem. In addition, different conflicting objectives may have to be considered when defining a screw configuration and, thus, it is usually tackled as a multi-objective optimization problem. In this research, a multi-objective ant colony optimization (MOACO) algorithm was adapted to deal with the TSCP. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Depending on the desired shear level and operating speed, two screws can be designed in different configurations 52 , 291 of co-rotating (rotating in the same direction) or counter-rotating (rotating in the opposite direction), depending on the desired mixing intensity. Co-rotating screws are usually used in pharmaceutical manufacturing because they generate relatively lower shear forces than the counter-rotating 266 .…”
Section: Manufacturing Methods For Preparing Amorphous Solid Dispersionsmentioning
confidence: 99%
“…Depending on the desired shear level and operating speed, two screws can be designed in different configurations 52 , 291 of co-rotating (rotating in the same direction) or counter-rotating (rotating in the opposite direction), depending on the desired mixing intensity. Co-rotating screws are usually used in pharmaceutical manufacturing because they generate relatively lower shear forces than the counter-rotating 266 .…”
Section: Manufacturing Methods For Preparing Amorphous Solid Dispersionsmentioning
confidence: 99%
“…Using a specific screw configuration, the group demonstrated that crystallinity of sildenafil citrate could be preserved with successfully processed formulations. In addition, Teixeira et al [45] investigated algorithmic tools that are effective and employed by the pharmaceutical industry. They also determined appropriate screw configurations for specific purposes.…”
Section: Hot Melt Extrusionmentioning
confidence: 99%
“…When the evaluation of candidate solutions is very costly in terms of computation time, usually only a small number of candidates can actually be evaluated. Costly solution evaluation arises in the case of simulation-based optimization [6] and, frequently, in industrial settings [44,129]. Applications with very small evaluation budgets have been rarely studied in the ACO literature, and preliminary results suggest that typical ACO parameter settings are not appropriate in such context [109].…”
Section: Aco and Surrogate Modelsmentioning
confidence: 99%